2019
DOI: 10.1002/iub.2030
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of KIF18A promotes cell proliferation, inhibits apoptosis, and independently predicts unfavorable prognosis in lung adenocarcinoma

Abstract: Kinesin family member 18A (KIF18A), as a member of the kinesin superfamily, is significantly overexpressed and abnormally functions in various human cancers. But, its expression profiling in the lung adenocarcinoma (LUAD) remains unclear. In the present work, using the data derived from the Cancer Genome Atlas (TCGA), we assessed the expression pattern and prognostic value of KIF18A in LUAD. In addition, we analyzed the underlying mechanism of its gene dysregulation. Experimental and bioinformatic analysis res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 36 publications
(42 reference statements)
2
24
0
Order By: Relevance
“…TGCTs are the most common solid tumours in young men, and their incidence is on the rise (Rosen et al, 2011). Our finding that KIF18A depletion inhibits proliferation of TCam-2 cells, is consistent with previous reports showing KIF18A-stimulated proliferation of other cancer cells in vitro and in vivo, such as clear cell renal carcinoma, breast cancer or lung adenocarcinoma (Chen et al, 2016;Zhang et al, 2010;Zhong et al, 2019). In addition, the effect of KIF18A depletion, associated with upregulation of apoptosis and cell cycle arrest represent features promoting cancer.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…TGCTs are the most common solid tumours in young men, and their incidence is on the rise (Rosen et al, 2011). Our finding that KIF18A depletion inhibits proliferation of TCam-2 cells, is consistent with previous reports showing KIF18A-stimulated proliferation of other cancer cells in vitro and in vivo, such as clear cell renal carcinoma, breast cancer or lung adenocarcinoma (Chen et al, 2016;Zhang et al, 2010;Zhong et al, 2019). In addition, the effect of KIF18A depletion, associated with upregulation of apoptosis and cell cycle arrest represent features promoting cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Since it was reported that KIF18A influences mouse germ cell proliferation (Czechanski et al, 2015;Luo et al, 2018;Zhong et al, 2019), we first investigated whether human KIF18A induces such an effect on TCam-2 cells, a cell line that originates from male germ cells. For that purpose, we performed an MTS proliferation assay upon KIF18A knockdown, starting at 24 h up to 120 h post transfection.…”
Section: Knockdown Of Kif18a Causes a Decrease In Proliferation Of Tcmentioning
confidence: 99%
“… 2 However, most patients relapse within 5 years, and treatment options are limited. 13 , 14 Accurate molecular characterization of abnormal gene expression involved in the development and progression of lung cancer is essential for identifying novel molecular targets of non-small cell lung cancer (NSCLC), which may improve future clinical outcomes. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Among the regulators that were not finally selected, there were also some well-known factors that had been declared in cancer. Silencing KIF18A induced apoptosis in lung adenocarcinoma cells and blocked the cell cycle at G2/M phase, while overexpression of KIF18A might promote cell proliferation and inhibit apoptosis [35]. Moreover, Kim et al suggested that CYP4A11 expression was a potential poor prognostic factor of renal cell carcinoma [36].…”
Section: Biomed Research Internationalmentioning
confidence: 99%